EasyReader: Text Reader for Visually Impaired People - Abdullah, Amirul; Mohd Rosli, Mohamad Amir Fahmi; Salleh, Norsaremah (International Journal on Perceptive and Cognitive Computing, 2022)
Text-to-speech helps many visually impaired people to read text easily. One of the commonly used tool is Google Text-to-Speech. It exists in most of the Android smartphones. However, it is just an engine to be used in another application such as google play books and google translate. It is limited to read certain books that are available in google play books. On google translate, we need to manually type the word in google translate application to convert it to voice. The method is not practical for visually impaired people. Hence, this study aims to develop a Text-to-Speech (TTS) application that visually impaired people can easily use. The system is made up with minimal number of easily spotted buttons and employed rather a simple step